2015
DOI: 10.1590/1807-57622014.0083
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura, organização e processos de trabalho no controle da tuberculose em municípios do estado do Rio de Janeiro, RJ, Brasil

Abstract: Em 2011, o estado do Rio de Janeiro (ERJ) apresentou a mais alta taxa de incidência de tuberculose do país. Realizamos uma pesquisa qualitativa sobre a estrutura, a organização e os processos de trabalho no Programa de Controle da Tuberculose (PCT), por meio de uma análise temática de entrevistas com coordenadores do PCT em 13 municípios do ERJ. A descentralização do controle da tuberculose – por intermédio da incorporação de suas normas pela Estratégia de Saúde da Família (ESF) – exige a reorganização dos pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
21

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 7 publications
3
8
0
21
Order By: Relevance
“…In Pelotas, most units did not have these materials, a situation also found in studies conducted in Rio de Janeiro (7) and Paraíba (5) . Despite the absence, the professionals were unanimous, during the qualitative analysis in Pelotas, in saying how easy it was to restock the input.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…In Pelotas, most units did not have these materials, a situation also found in studies conducted in Rio de Janeiro (7) and Paraíba (5) . Despite the absence, the professionals were unanimous, during the qualitative analysis in Pelotas, in saying how easy it was to restock the input.…”
Section: Discussionmentioning
confidence: 54%
“…The proximity to a reference professional and a bond of trust established with the health unit favor the search for care when the first symptoms appear, leading to an early diagnosis. A study conducted in the Rio de Janeiro state (7) , in 2015, revealed that one of the main difficulties in keeping the TB control actions decentralized and in the PHCs is the turnover of professionals, since it is impossible to maintain the program active in a unit where the professionals are not made aware of TB and trained to deal with it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Achados de outros estudos corroboram sobre a carência de insumos fundamentais às práticas do PCT, como o de Cunha et al (2015), que reforça a questão em municípios do estado do Rio de Janeiro, dentre eles o de Itaboraí.…”
Section: Programa De Controle Da Tuberculoseunclassified